Nuestra America - Konrad, Kristina (Germany : Seitler, Cornelia ; Hofer, Brigitte, 2005)
Returns to Nicaragua twenty-five years after a revolution which nobody believed was possible. In 1979, the Latin American country had just freed itself from a 45-year dictatorship and was attempting the impossible, encountering the bitter hostility of big-brother to the north, the USA. Nicaragua hoped to triumph over poverty and discrimination, within a system of political plurality and a mixed economic system, while remaining independent of world political blocs. Kristina Konrad, who lived and worked in Nicaragua during the 1980s returns to a neo-liberal country, battered by war and corruption and sketches a narrative of memories and observations of the current state of affairs. "Our America" looks at the lives of women who took up arms during the revolution and in the fight against the US-funded Contras and how they now struggle to survive today. What remains from the dream for independence and justice?
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films